مستوى مراعاة معلمي المرحلة الأساسية الدنيا لمعايير نموذج دن و دن Dunn and Dunn لأنماط التعلم وعلاقته بميولھم نحو مھنة التدريس - عبدالجواد، إياد ابراهيم (جامعة النجاح الوطنية, 2016)
هدفت الدراسة إلى تعرف مستوى مراعاة معلمي المرحلة الأساسية الدنيا لمعايير نموذج (دن و دن) لأنماط التعلم، والفروق في هذا المستوى التي تعزى لمتغيرات الجنس، وسنوات الخدمة، والصف الدراسي، كما هدفت إلى تعرف مستوى ميول معلمي المرحلة الأساسية الدنيا نحو مهنة التدريس، والفروق فيها التي تعزى لمتغيري الجنس، وسنوات الخدمة، وسعت الدراسة إلى الكشف عن العلاقة بين مستوى مراعاة معلمي المرحلة الأساسية الدنيا لمعايير نموذج (دن و دن) لأنماط التعلم، وميولهم نحو مهنة التدريس. ولتحقيق أهداف الدراسة قام الباحث ببناء أداتين، الأولى: استبانة المعايير، الثانية: مقياس الميول نحو مهنة التدريس، وتم تطبيق أداتي الدراسة على عينة عشوائية بلغت (144) معلما ومعلمة، وتوصلت الدراسة إلى عدة نتائج منها: - بلغ الوزن النسبي لمستوى مراعاة معلمي المرحلة الأساسية الدنيا لمعايير نموذج (دن ودن) لأنماط التعلم على محاور الاستبانة ككل (77.3%). - لا توجد فروق دالة إحصائيا في مستوى مراعاة معلمي المرحلة الأساسية الدنيا لمعايير نموذج ردن و دن) تعزى لمتغيرات (الجنس، وسنوات الخدمة، والصف الذي يدرسه المعلم). - بلغ الوزن النسبي لمستوى ميول معلمي المرحلة الأساسية الدنيا نحو مهنة التدريس (73.0%). - لا توجد فروق دالة إحصائيا في مستوى ميول معلمي المرحلة الأساسية الدنيا نحو مهنة التدريس تعزى لمتغيري (الجنس، وسنوات الخدمة). - وجود علاقة إيجابية بين مستوى مراعاة معلمي المرحلة الأساسية لمعايير نموذج (دن ودن)، وميولهم المهنية نحو مهنة التدريس.
The study aimed to identify the level of concerning the standards of (Dunn and Dunn) model of learning styles by elementary teachers, and the differences of this level, due to the (gender, years of service and grade). Also, it aimed to identify the level of teachers' tendencies towards teaching profession, and the differences of this level due to the variables (gender and years of service), and in addition it aimed to find out if there is a relationship between the level of concerning the standards of (Dunn and Dunn) model of learning styles and teachers' tendencies towards teaching profession. To achieve the objectives of this study, the researcher prepared two tools: The first one was the questionnaire of the standards, and the second was the scale of teachers' tendencies towards teaching profession. The two tools were applied on a random sample of (144) teachers (Males and Females). The researcher reached several conclusions, including: - The Weight relative of the level of concerning the standards of (Dunn Dunn) model of learning styles in the whole questionnaire was (77.3%). - There is no statistically significant differences in the level of using the standards of (Dunn and Dunn) model due to the variables (gender - years of service - class taught by a teacher). - The relative weight of the level of teachers' tendencies towards teaching profession was (73.0%). - There is no statistically significant differences in the level of teachers' tendencies towards teaching profession due to the variables (gender - years of service). - There is a relationship between the level of concerning the basic standards of (Dunn Dunn) model of learning styles and teachers' tendencies towards the teaching profession.
Keywords: المعايير التربوية -- الأنماط التعليمية -- معلمو المرحلة الأساسية -- الميول التدريسية